Analysis of Determinant Factors of Hygiene Behavior: The handler Food in the Home Food Industry (P-IRT) - Herawati, Cucu; Sutarsih, Cicih; Indragiri, Suzana; Ratnawati, Dewi; Aurel Safitri, Keisha (Indonesian Journal of Multidisciplinary Science, 2026)
Problem health, specifically problem hygiene and sanitation, food is a very complex problem. Around 70% of cases of poisoning from food in the world are caused by food Ready dining. Research objectives. This For analyze factor determinant behavior hygiene handler food in the Home Food Industry (P-IRT). Study: This use type study survey analysis with Cross Sectional approach. The population that is all over Home Industry Food Places (P-IRT) and handles food in the Puskesmas area, Source Cirebon Regency in 2024. The sample used in the study. This is the total sample, totaling 90 samples handler food. Data collection with interviews and observations through a tool measuring questionnaire. Research results: There is a connection between knowledge (p-value 0.005) and facilities and infrastructure (p-value 0.008) with behavior hygiene handler food. There is no connection between training with behavior hygiene handler food (p-value 1.000). Officer health should increase activity effort promotion with give education to handlers about behavior hygiene and handler food.  Handler food should expand his knowledge with further training, and management should provide the means to lack of support .